ANALISA KEKUATAN WELDING REPAIR BAJA AISI 420 DENGAN METODA GMAW - Cecep Slamet Abadi; Rosidi Rosidi; Idrus Assagaf (Politeknik Negeri Jakarta, 2019)
Welding technology is used because besides being easy to use, it can also reduce costs so it is cheaper. Especially for welding repair. From the welding repair the extent to which the strength of GMAW welds can repair components from the molded plastic mold room made of AISI 420 stainless steel. Repair of the print room components using deposit welding is tested using tensile strength and hardness as realization of resistance when holding the rate of liquid plastic entering the print room by 25 to 40 MPa, depending on the plastic viscosity, the precision of the mold and the filling level of the print room. Deposition welding method as a welding repair can affect a procedure to be able to produce a component that is safe and capable of being used in accordance with the provisions. The welding process used is reverse polarity GMAW DC with 125 A current and ER 70 S welding wire diameter 1.2 mm. Test material AISI 420. Tests carried out were tensile test, impact test and hardness test in weld metal, HAZ and base metal. From the Charpy impact test and tensile test obtained the value of welding strength which is close to the strength of the complete object, which is equal to 65%. The energy absorbed by the impact test object with GMAW welding is 5.4 Joule while for the whole test object is 8.1 Joule. The welding tensile strength is 520 MPa compared to the tensile tensile strength of 820 MPa.